Structural studies of the primary donor cation radical P(870)(+·) in reaction centers of Rhodospirillum rubrum by electron-nuclear double resonance in solution - Lubitz, W. (1984)
The light-induced cation radical of the primary electron donor, P(870)(+·), in photosynthetic reaction centers from Rhodospirillum rubrum G-9, has been investigated by electron-nuclear double resonance (ENDOR) in liquid aqueous solution. The measured hyperfine coupling constants are assigned to specific molecular positions by partial deuteration. Comparison with the bacteriochlorophyll a cation radical shows different reduction factors of the individual coupling constants deviating from the value 2.0 reported in earlier investigations in frozen solutions. The average of the coupling constants is, however, reduced by a factor very close to 2.0. EPR simulations using the ENDOR coupling constants support a dimer model for P(870)(+·) with C(2) symmetry, where the two macrocycles are close enough to form a supermolecular orbital resulting in a different distribution of the unpaired electron, compared with the monomeric bacteriochlorophyll a cation radical. Molecular orbital calculations were used to obtain structural information about this dimer.